The German right in the Weimar Republic : studies in the history of German conservatism, nationalism, and antisemitism - Jones, Larry Eugene 1940- HerausgeberIn (Berghahn, 2014)
Hindenburg and the German right / Wolfram Pyta -- From friends to foes: Count Kuno Von Westarp and the transformation of the German right / Daniela Gasteiger -- Conservative antisemitism in the Weimar Republic: a case study of the German National People's Party / Larry Eugene Jones -- Academics and radical nationalism: the Pan-German League in Hamburg and the German reich / Rainer Hering -- Realms of leadership and residues of social mobilization: the Pan-German League, 1918-1933 / Bjorn Hofmeister -- Continuity and change on the German right: the Pan-German League and nazism, 1918-1939 / Barry A. Jackisch -- Weimar's "burning question": situational antisemitism and the German combat leagues, 1918-1933 / Brian E. Crimm -- Antisemitism and the "Jewish question" in the political worldview of the Catholic right / Ulrike Ehret -- Eugenics and Protestant social thought in the Weimar Republic: Friedrich Von Bodelschwingh and the Bethel institutions / Edward Snyder -- Carl Schmitt and the Weimar right / Joseph W. Bendersky